Juridical Analysis of the Determination of Jurisdiction and Its Legal Consequences for Consumer Protection in Cross-Border Digital Transactions Based on Electronic Contracts - Aurelia Jessica Mavelynn (Media Hukum Indonesia (MHI), 2026)
The rapid development of information technology has accelerated the growth of cross-border digital transactions conducted through electronic contracts involving business actors and consumers from different jurisdictions. This situation gives rise to legal issues concerning the determination of jurisdiction and its legal consequences for consumer protection. This study aims to examine the determination of jurisdiction in resolving disputes arising from cross-border digital transactions and to analyze its legal consequences for consumer protection. The research employs a legal research method using statutory and conceptual approaches, based on a literature study of primary, secondary, and tertiary legal materials analyzed qualitatively. The findings indicate that the determination of jurisdiction in cross-border digital transactions encounters challenges due to the limitations of applying traditional private international law principles within the digital environment. The use of choice of forum and choice of law clauses in electronic contracts tends to place consumers in a weaker position, potentially limiting their access to justice. The legal consequences of jurisdiction determination are reflected in the application of certain laws that may not provide adequate consumer protection, restricted access to dispute resolution mechanisms, and difficulties in the enforcement of foreign judgments. Existing national legal frameworks have not fully addressed these complexities, thus requiring regulatory enhancement and international cooperation to ensure more effective consumer protection in cross-border digital transactions.